Perl for exploring DNA - LeBlanc, Mark D., 1962-; Dyer, Betsey Dexter (Oxford : Oxford University Press, 2007)
This book provides an introduction to Perl that emphasizes good programming practices with repeated exposure to pattern matching as applied to biological sequence analysis (DNA analysis, protein analysis).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nucleotide sequence -- Data processing; Amino acid sequence -- Data processing; Perl (Computer program language)